1972
DOI: 10.1007/bf01394520
|View full text |Cite
|
Sign up to set email alerts
|

Excitation functions for the production of90Nb and88Y by irradiation of zirconium with deuterons

Abstract: The compound-statistical model plus Hittmair's stripping theory accounts quite well for the (d, 2n) cross sections observed. However, the agreement obtained with Peaslee-Otozai's theory is excellent and the set of parameters used more reasonable. It has been assumed that the stripping mechanism can have no contribution to the (d, e) reaction. Accordingly, calculations for this reaction have been done using the compound-statistical model and the entire absorption process followed by the evaporation of an c~ par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The deuteron activation cross sections were studied previously in [17][18][19][20]. We obtained preliminary data for 10 excitation functions that are in agreement with previous authors.…”
Section: D+zrsupporting
confidence: 84%
“…The deuteron activation cross sections were studied previously in [17][18][19][20]. We obtained preliminary data for 10 excitation functions that are in agreement with previous authors.…”
Section: D+zrsupporting
confidence: 84%
“…In fact even a small-sized cyclotron (E p ≤ 16 MeV) should lead to sufficient quantities of the radioisotope via the ( p, n)-reaction. A few studies have shown that the (d, 2n)-reaction requires a deuteron energy of about 16 MeV [5][6][7], the ( 3 He, 2n)-process a 3 Heenergy of ≥ 30 MeV and the (α, 3n)-reaction an α-particle energy of ≥ 45 MeV [8]. Furthermore, the systematics of ( 3 He, 2n)-and ( p, n)-reactions suggest that the production yield of 90 Nb should be higher in the latter process.…”
Section: Introductionmentioning
confidence: 99%